Application of Digital Entrepreneurship Education in the Digital Library Marketing Course - Siti Rohaya; F. Trisakti Haryadi; Alia Bihrajihant Raya (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2022)
Entrepreneurship education in universities plays a significant role in creating an entrepreneurial spirit in students. We explore the application of digital entrepreneurship education contained in the Digital Library Marketing course. This research is qualitative research with a case study. Data collection was conducted through in-depth semi-structured interviews with thirteen informants. The data are photos or videos of activities during the research, and videotape recordings. The data display the output of Digital Library Marketing lectures which shows how theories following research and observation of digital media interfaces are used as promotional and marketing media. The results showed that digital entrepreneurship education applied to the Digital Library Marketing course has an important influence on students to design a professional weblog as a medium of information, to create content writing about how to fill a weblog that can sell the products offered, and to do good copywriting, also to find ideas for delivery and promotion. Besides being applied to the Digital Library Marketing course, digital entrepreneurship education is also held in digital marketing workshops to provide prospective alums. This study is helpful for entrepreneurship education literature in libraries and information that intersects with digital technology as a medium for entrepreneurship.